Desenvolvimento de drageado de soja [Glycine max (L.)] com cobertura crocante e salgada - Schena, Deivid Padilha (2016)
O Consumption of soy products has increased in Brazil, leading to improvements in sensorial characteristics and product diversity. Soy is a food for animals, a product for human consumption, a product for health and a health system. The population has little acceptance of functional products, especially when sensory is not pleasant. With this, the objective of the work was elaborated based on coverage with food and salt coverage. In the preliminary tests, three formulations, formulation 1, with addition of 5% oat flour, formulation 2 with 15% oat flour and formulation 3 with 25% oat flour were defined. The dragees were on proximal composition, microbiological analyzes, sensory and texture acceptance. In the three formulations, there was no significant difference in the proximal composition, indicating lower lipid values when compared to commercial products. For the dietary fiber, the developed product obtained high values when compared to products based on soybeans and mainly soybeans in grains, with emphasis on formulations 2 and 3. The result for the dietary fibers had values higher than expected, where in Brazilian legislation Product to be assisted with high fiber content and functional claim needs to contain at least 6%, where formulation 3 obtained the value of 14.5%, and the content of insoluble fibers more expressive. The results of the microbiological analyzes proved that the product was developed and framed in the Brazilian legislation. As sensory analysis of the dragees indicate that the product had good acceptance in color and texture, obtaining notes of "I liked" a "moderately" and for overall taste and acceptance of "liked" a "moderately liked". In the index of acceptability, they indicated a mean above 70%, mainly in formulation 2, where it obtained the highest index in the average, 74.5%. The instrumental texture analysis of the dragees showed no differences between the formulations evaluated and the values obtained in the product developed during the comparison period when the product is marketed or japanese type peanuts.